Development of a mitochondria-targeted fluorescent probe for the ratiometric visualization of sulfur dioxide in living cells and zebrafish. Issue 31 (29th July 2019) - Yang, Yunzhen; He, Longwei; Xu, Kaixin; Lin, Weiying
Abstract : A new mitochondria-targeted fluorescent probe was engineered for the ratiometric visualization of sulfur dioxide in living cells and zebrafish. Abstract : Herein, a mitochondria-targeted ratiometric fluorescent probe for SO2 was proposed based on the FRET coumarin–phenylchromenylium dyad. The probe showed two distinct emission bands centered at 485 and 650 nm. Upon exposure to SO2, the acceptor emission was inhibited, and a significant enhancement in donor fluorescence was simultaneously induced; this resulted in a satisfactory ratiometric fluorescence signal. Importantly, the probe was biocompatible and successfully applied to monitor SO2 in live HeLa cells and zebrafish.